Aphasia and related neurogenic communication disorders - Papathanasiou, Ilias; Coppens, Patrick, 1944- (Burlington, MA : Jones & Bartlett Learning, 2022)
'Reviews the definition, term, classification, symptoms, and neurology of aphasia, including theories of plasticity and recovery.' -From publisher.
Aphasia and related neurogenic communication disorders: basic concepts, management, and use of technology -- Significant landmarks in the history of aphasia and its therapy -- Neurology, connectivity, and the nature of aphasia -- Plasticity and recovery in aphasia -- Formal and informal assessment of aphasia -- Therapy approaches to aphasia -- Treatment efficacy and therapy outcomes -- Extralinguistic cognitive considerations in aphasia management -- Disorders and management of auditory comprehension -- Disorders of word production -- Acquired disorders of reading: modeling, assessment, and treatment -- Written language and its impairments -- Disorders of sentence processing in aphasia -- Approaches to assessment and treatment of everyday talk in aphasia -- Quality-of-life approach to aphasia -- Living with aphasia: a client-centered approach -- Aphasia management in ethnoracially diverse multilingual populations -- Related communication disorders -- Communication disorders associated with right-hemisphere brain damage -- Cognitive disorders associated with right-hemisphere brain damage -- Traumatic brain injury -- Dementia and related cognitive disorders -- Living with cognitive-communication disorders -- Language disorders in neurosurgery -- Acquired apraxia of speech -- Management of dysarthria.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on June 16, 2021).
WorldCat record variable field(s) change: 650
Keywords: Aphasia; Communicative disorders; Language disorders; Evidence-based medicine; Aphasia; Communication Disorders; Evidence-Based Practice; Language Disorders; Aphasie; Troubles de la communication; Troubles du langage; Médecine factuelle; Aphasia; Communicative disorders; Language disorders; Electronic books; Electronic books